Sustainable Power Systems Modelling, Simulation and Analysis - Karki, Nava Raj; Karki, Rajesh; Verma, Ajit Kumar; Choi, Jaeseok (Reliable and Sustainable Electric Power and Energy Systems Management, 2017)
XIV, 174 p. 76 illus.